Developmental disturbances associated with agenesis of the permanent maxillary lateral incisor - Pinho, T. (2009)
The aim of this study was to characterise the intra and extra-oral phenotype associated with agenesis of the permanent maxillary lateral incisor. We compared three groups: (1) subjects with agenesis of one or both permanent maxillary lateral incisors (n=80); (2) first and second degree relatives of group 1 with no agenesis of the permanent maxillary lateral incisor and (3) subjects with no agenesis of the maxillary lateral incisor or family history of it (n=49). For each of the 201 subjects detailed clinical information was reviewed and panoramic radiographs were analysed. Considering only the sample with unilateral agenesis, microdontia of the contralateral permanent maxillary lateral incisor was significantly more frequent in group 1 (82.4%) than in group 2 (25%) and the control group (2%). This supports the theory that microdontia is a variable expression of the same developmental disturbance that causes tooth agenesis. The absence of third molars occurred more often in group 1 (36.2%) than in groups 2 and 3 (18.6% and 18.9% respectively), confirming that agenesis of third molars was markedly associated with the agenesis of the permanent maxillary lateral incisor. Agenesis of teeth other than third molars was not significantly different among subjects with agenesis of the permanent maxillary lateral incisor and their relatives. The frequencies of supernumerary teeth, permanent maxillary canine impaction, general health condition and minor anomalies were not significantly different between the three groups.